Impact tests in pure and aerated water - Lange, Niels A.; Rung, Thomas (ASME, 2011)
Impact loads due to slamming or ditching are an important issue in marine and aircraft engineering. Accordingly, many experimental, theoretical and numerical investigations have been performed. The paper reports the build-up of a test rig, which was designed to study vertical guided motion impact tests, and the results of an experimental study on impact loads into pure and aerated water. Attention is given to the loads experienced by a rigid circular-cylinder section (diameter=0.2 m, length=0.5 m) during guided, constant-speed impact. The investigations involve a variety of entry speeds up to 3m/s and gas-content levels. The obtained data offers a basis for an analysis of the sensitivity of the impact loads on the gas content. Fair compliance with literature reported experimental and theoretical results - using e.g. von Kármán or Wagner theories - has been obtained for pure water impact loads. For impact tests in aerated water, a significant reduction of the measured pressure peaks becomes apparent. Finally, the paper illustrates the feed back of the experimental results into an impact-load model, taking the fluid compressibility into account.